The Impact of Losing Your Job - Ehlert, Martin (Amsterdam University Press, 2016)
Losing a job has always been understood as one of the most important causes of downward social mobility in modern societies. And it's only gotten worse in recent years, as the weakening position of workers has made re-entering the labour market even tougher. The Impact of Losing Your Job builds on findings from life course sociology to show clearly just what effects job loss has on income, family life, and future prospects. Key to Ehlert's analysis is a comparative look at the United States and Germany that enables him to show how different approaches to welfare state policies can ameliorate the effects of job loss-but can at the same time make labour insecurity more common.